Biology and key to the Australian species of Hypogastrura and Ceratophysella (Collembola: Hypogastruridae). Issue 1 (16th September 2013) - Greenslade, Penelope; Ireson, John; Skarżyński, Dariusz
Abstract The family Hypogastruridae is represented by nine genera in Australia, three of which: Mesogastrura Bonet, Hypogastrura Bourlet and Ceratophysella Börner, consist only of species that have been probably introduced from Europe within the last 250 years, with the exception of a new species described here. All species in these three genera are typical of, and abundant in, disturbed habitats. The 11 species currently recorded from Australia in Hypogastrura and Ceratophysella are C. communis (Folsom, 1897), C. denticulata (Bagnall, 1941), C. gibbosa (Bagnall, 1940), C. succinea (Gisin, 1949), Hypogastrura assimilis (Krausbauer, 1898), H. distincta (Axelson, 1902), H. manubrialis (Tullberg, 1869), H. purpurescens (Lubbock, 1867, H. vernalis (Carl, 1901) and H. viatica (Tullberg, 1872), and a new species C. pauciseta sp. nov. Ceratophysella communis was misidentified in some published literature as C. engadinensis Gisin, 1949. Although C. communis is confirmed as occurring in Australia, there now seems to be no evidence that C. engadinensis occurs here, and the name H. denticulata may include more than one species. An illustrated dichotomous key and description is given here for all Australian species of Hypogastrura and Ceratophysella, and their distributions and habitats documented. Their value as indicators of disturbed habitats in Australia is discussed. Collembola in general have been shown to have a positive influence on nutrient cycling. It is not known what contribution Hypogastrura and Ceratophysella make to Australian arable and grazing systems in this respect, but it may be considerable because of their abundance.